„Weiter leben und doch nicht Sieger sein": Elias Canettis existentiell-poetologisches Selbstverständnis als „Tod-Feind" und „Hüter der Verwandlungen" - Przybecki, Marek (Studia Germanica Posnaniensia, 2018)
This text is an attempt at rationalization of as it would seem - an irrational poetological conception of Canetti expounded in the essay „The profession of a poet“. Anthropological thought of the author of „Crowds and Power“ in which man appears as a being possessed by the greed of power felt in the most perceivable way at the moment of experiencing the deaths of other beings - there is a collision with the poet's vision whose main task is according to Canetti opposing all power and all violence born in the field of social influence of death. Hostility towards death is not therefore a theoretical gesture of mutiny in Canetti against an inevitable dying of cells, but an expression of the rational rejection of the process of social domestication of death. The remedy to this phenomenon is perceived by Canetti in the ability inborn in a primitive man and lost in the process of civilization to metamorphosis which ability the writer should just develop in himself and in others, taking from the reservoir of human experiences contained in myths and in old literary works.